Constraints Analysis of Village Panchayat Members in Their Job Performance in Banaskantha District of Gujarat State - Kuldeep Singh , R. R. Prajapati and M.R. Prajapati, (Indian Journal of Extension Education, 2015)
The present study was conducted in Banaskantha district of Gujarat state. Palanpur and Dantiwada talukas were selectedrandomly. All the 20 samras village panchayats of both the selected talukas were selected purposively. The Panchayatmembers from each village were selected using proportionate random sampling technique making a sample of 120panchayat members as respondents. The constraints experienced by village panchayat members were assessed againstfive aspects. The constraint perceived as hindering the job performance was rated by the respondents on a three pointcontinuum viz., very effective, moderately effective and less effective with scores of 3, 2 and 1, respectively. Further foridentifying the overall important constraints and aspects-wise important constraints, the total weighted score for eachconstraint were computed. The most important constraints in job performing of the village panchayat members havingmean score more than the overall mean score (2.14) in order of importance were; 'inadequate fund allotted fromgovernment for development work', 'lack of training to the village panchayat members', 'delay in sections from upperauthority', 'lack of honorarium to the panchayat members working at village level', 'lack of knowledge regarding PRS anddevelopment programmes', 'no work initiated without giving bribe', 'lack of administrative and financial power to thevillage panchayat members', 'lack of experience as leader', 'lack of information regarding different rural developmentprogrammes', 'groupism encouraged by members', 'lack of communication facility at village level', 'low level ofeducation'. The important suggestions endorsed by the village panchayat members were; 'amount of grant should beincreased', 'training on village developmental activities should be provided to village panchayat members', 'training onleadership development and functioning of PRIs should be provided to village panchayat members', 'office procedureshould be more quick, easy and in time' and 'honorarium should be given to village panchayat members'.